Managing Diversity in India: Evaluating the Effectiveness of Workforce Diversity Initiatives of Three U.S. Based Multinational Corporations in India - Batra, Ashima (2007)
Managing diversity has emerged as a significant management practice, conceptualised to tackle the growing number of employee equality and equal opportunity related complexities. The changing nature of work practices due to globalisation has brought to the forefront workplace diversity issues. The origins and conception of diversity in the U.S. and India forms the basis for analysing an originally American concept in an Indian context. The two countries offer an exciting backdrop given the political, social, economic and cultural differences. To further understand the diffusion of workplace diversity practices in India, the study conducts a comprehensive analysis on the diversity activities of three prominent U.S. based Multinational Corporation's (MNCs) that have a strong presence in India. Multinationals have substantial influence on internationalising Human Resource Management practices and as a result, have influenced the growing popularity of diversity management and workforce diversity in India. The study examines company reports and online media releases to evaluate the effectiveness of diversity plans. The MNCs success is measured by the ability to adapt their initiatives to meet the requirements of the local Indian environment, by an understanding of what workforce diversity entails in the Indian scenario. The research findings suggest that the initiatives are responsive to local conditions, but are guided by the overarching company definitions and frameworks for diversity.